2020
DOI: 10.1002/mde.3142
|View full text |Cite
|
Sign up to set email alerts
|

Design versus utility innovation: Is corruption sanding or greasing the wheels of innovation?

Abstract: This paper studies whether corruption has a greasing or a sanding effect on the production of innovation. The main novelty lies in comparing the relative impacts on design versus utility innovation. On the one hand, corruption can undermine (sand) the expected returns from patents, whereas on the other hand, patent holders might be able to increase (grease) the scope and applicability of their patents. Using U.S. state-level data and controlling for bidirectional causality, results show the sanding effect of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…These findings can be seen as complementary to results in the literature that show corruption to facilitate the market introduction of innovations (Goel & Nelson, 2018). On the other hand, when a distinction is made between design and utility patents, the greasing effect of corruption on innovation production does not necessarily hold, at least not for the United States-see Goel and Saunoris (2020). From a broader policy perspective, these spillovers from corruption might make a case for tolerating some level of corrupt activity.…”
Section: Discussion Of Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…These findings can be seen as complementary to results in the literature that show corruption to facilitate the market introduction of innovations (Goel & Nelson, 2018). On the other hand, when a distinction is made between design and utility patents, the greasing effect of corruption on innovation production does not necessarily hold, at least not for the United States-see Goel and Saunoris (2020). From a broader policy perspective, these spillovers from corruption might make a case for tolerating some level of corrupt activity.…”
Section: Discussion Of Resultssupporting
confidence: 59%
“…The greasing effect of corruption has some support in the literature, albeit in studies focusing on different aspects of technological change. Goel and Nelson (2018) found that corruption greased the introduction of process innovations to the market across countries, while, considering data across U.S. states and distinguishing between design and utility patents, Goel and Saunoris (2020) show that the greasing effect of corruption does not hold, and the influence of the timing of corruption effects is sensitive to the type of innovation considered. The current paper, on the other hand, considers the impact of corruption on the efficiency in the production of innovations.…”
Section: Full Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Greater corruption may act as an impediment or an enabler to firms' operations (Goel & Saunoris, 2020). Third, the presence of informal sector firms (INFORMAL), who do not pay taxes or adhere to regulations and undermine potential payoffs from research, is another indication of weak institutions.…”
Section: Empirical Modelmentioning
confidence: 99%
“…In addition, corruption could affect product and process innovation activities. For example, public officials may ask for bribes from product innovators in exchange for granting a patent for a newly developed product (Goel & Saunoris, 2020). In the context of process innovation, corruption could affect the probability of process innovation taking place (Goel & Nelson, 2018) by increasing the costs of firms' investments in machinery, which are important to introducing innovations (Paunov, 2016).…”
Section: Introductionmentioning
confidence: 99%